The Complexity Paradox: Why Digital Startups Simplification Efforts Generate Escalating Organisational Demands - Dip, Jose Martin (Digital Repository of Theses, 2026)
Digital-native ventures face a paradox: tools meant to simplify operations generate complexity. Buffer's platform count grew from 12 to 47 in six years, and GitLab's from 8 to 127 over a decade, with platform-related work consuming 28-35% of engineering capacity that should support product development (Buffer, 2020; GitLab, 2021). Traditional organisational theory offers little explanation. Lifecycle models suggest that growing firms move toward stability; platform scholarship emphasises how digital tools reduce coordination costs; and institutional theorists argue that conformity reduces uncertainty. Yet digital startups experience precisely the opposite. This research identifies three mechanisms driving recursive complexity. Digital artefact genealogy explains how each platform adoption spawns 2 to 4 descendant technologies across 5 to 7 generations. When Buffer adopted Salesforce, it required integration middleware, which needed governance protocols, which demanded monitoring tools. Institutional logic cascading shows how conformity amplifies exposure. GitLab's SOC 2 certification attracted the GDPR authorities, then labour regulators, and finally tax agencies, each with incompatible requirements. Liquid-solid oscillation acceleration describes why restructuring intervals compress from 4 years to quarterly cycles. Using digital process archaeology to reconstruct organisational evolution through versions, handbooks, code repositories, and timestamped documentation, the study tracked six digital ventures (GitLab, Buffer, Zapier, Notion, Airtable, Figma) over 6-11 years with temporal precision that retrospective interviews cannot provide. These mechanisms compound synergistically. Complexity is embedded in approximately 40 platforms and 10 institutional domains, regardless of business model. The resulting framework enables founders and investors to diagnose genealogical risks, map institutional exposure, and implement temporal governance, transforming complexity from invisible tax into a manageable dynamic.